2019
DOI: 10.1080/10408444.2019.1700210
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationships between lung cancer mortality rates, smoking, and ambient air quality: a comprehensive review and analysis

Abstract: Lung cancer mortality (LCM) has been associated with smoking and air pollution. This article draws on smoking relationships to clarify air pollution relationships. We analyzed cohort and population-based smoking studies and identified effects of latency and cumulative exposures. We found cogent relationships through longitudinal rather than cross-sectional analysis, thus involving historical data. We also considered passive smoking, occupational exposures, radon, and established carcinogens. We found stable no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 184 publications
(128 reference statements)
1
28
0
1
Order By: Relevance
“…1 Tissue injury is a known trigger of cancerogenesis for 2 reasons: (i) its potential to induce DNA damage and somatic mutations, especially in tissue-resident long-lived stem cells 2 ; and (ii) its potential to promote the expansion of such mutated cells during the process of tissue repair. 3 For example, these 2 mechanisms contribute to inflammatory bowel disease-related colorectal cancer 4 and to lung cancer related to exposures to toxic smokes and dust particulates, 5 atrophic gastritis-related gastric cancer, 6 and cirrhosis-related hepatocellular carcinoma. 7 Numerous epidemiologic studies report the association between chronic kidney disease (CKD) and kidney cancer (Table 1 [8][9][10][11][12][13][14][15] ).…”
mentioning
confidence: 99%
“…1 Tissue injury is a known trigger of cancerogenesis for 2 reasons: (i) its potential to induce DNA damage and somatic mutations, especially in tissue-resident long-lived stem cells 2 ; and (ii) its potential to promote the expansion of such mutated cells during the process of tissue repair. 3 For example, these 2 mechanisms contribute to inflammatory bowel disease-related colorectal cancer 4 and to lung cancer related to exposures to toxic smokes and dust particulates, 5 atrophic gastritis-related gastric cancer, 6 and cirrhosis-related hepatocellular carcinoma. 7 Numerous epidemiologic studies report the association between chronic kidney disease (CKD) and kidney cancer (Table 1 [8][9][10][11][12][13][14][15] ).…”
mentioning
confidence: 99%
“…Because of the low level of smoking among Swedish men, it is evident that the population attributable fraction of smoking for bladder cancer is declining, and other factors may exert a detectable role. Considering the lag time between smoking and bladder cancer of 20 to 40 years, smoking related bladder cancer should still be declining in Swedish men [ 3 , 4 ]. Thus, new factor(s) appear to counteract this decline.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence trends of lung and urinary bladder cancers have marked the cigarette smoking epidemic which started in various countries before or after World War II [ 1 , 2 ]. The incidence rates followed the consumption of cigarettes with a lag time of 20 to 40 years and have started to decline as the number of smokers has diminished [ 3 , 4 ]. Relative risks for tobacco-related lung cancer are of the order of 10 to 20 in active smokers compared to non-smokers, depending on pack-years smoked and other factors, and they remain at levels of 3–5 after 20 years of quitting [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the long-term mortality studies have interpreted positive responses as indicating that presence of outdoor ambient pollution caused new cases of chronic disease. I showed that this was not the case for lung cancer [39], because of neglecting timing effects and underestimating smoking effects. There have been few studies of long-term disease progression or morbidity [40].…”
Section: Cohort Subsetsmentioning
confidence: 99%